Cellular and molecular architecture of hematopoietic stem cells and progenitors in genetic models of bone marrow failure - Stephanie Heidemann; Brian Bursic; Sasan Zandi; Hongbing Li; Sagi Abelson; Robert J. Klaassen; Sharon Abish; Meera Rayar; Vicky R. Breakey; Houtan Moshiri; Santhosh Dhanraj; Richard de Borja; et al. (JCI Insight, 2021)
Inherited bone marrow failure syndromes, such as Fanconi anemia (FA) and Shwachman-Diamond syndrome (SDS), feature progressive cytopenia and a risk of acute myeloid leukemia (AML). Using deep phenotypic analysis of early progenitors in FA/SDS bone marrow samples, we revealed selective survival of progenitors that phenotypically resembled granulocyte-monocyte progenitors (GMP). Whole-exome and targeted sequencing of GMP-like cells in leukemia-free patients revealed a higher mutation load than in healthy controls and molecular changes that are characteristic of AML: increased G>A/C>T variants, decreased A>G/T>C variants, increased trinucleotide mutations at Xp(C>T)pT, and decreased mutation rates at Xp(C>T)pG sites compared with other Xp(C>T)pX sites and enrichment for Cancer Signature 1 (X indicates any nucleotide). Potential preleukemic targets in the GMP-like cells from patients with FA/SDS included SYNE1, DST, HUWE1, LRP2, NOTCH2, and TP53. Serial analysis of GMPs from an SDS patient who progressed to leukemia revealed a gradual increase in mutational burden, enrichment of G>A/C>T signature, and emergence of new clones. Interestingly, the molecular signature of marrow cells from 2 FA/SDS patients with leukemia was similar to that of FA/SDS patients without transformation. The predicted founding clones in SDS-derived AML harbored mutations in several genes, including TP53, while in FA-derived AML the mutated genes included ARID1B and SFPQ. We describe an architectural change in the hematopoietic hierarchy of FA/SDS with remarkable preservation of GMP-like populations harboring unique mutation signatures. GMP-like cells might represent a cellular reservoir for clonal evolution.